Rnd3 Expression is Necessary to Maintain Mitochondrial Homeostasis but Dispensable for Autophagy - Cueto-Ureña, Cristina; Mocholí, Enric; Escrivá-Fernández, Josep; González-Granero, Susana; Sánchez-Hernández, Sabina; Solana-Orts, Amalia; Ballester-Lurbe, Begoña; Benabdellah, Karim; Guasch, Rosa M.; García-Verdugo, José Manuel; Martín, Francisco; Coffer, Paul J.; et al. (Frontiers in Cell and Developmental Biology, 2022)
Autophagy is a highly conserved process that mediates the targeting and degradation of intracellular components to lysosomes, contributing to the maintenance of cellular homeostasis and to obtaining energy, which ensures viability under stress conditions. Therefore, autophagy defects are common to different neurodegenerative disorders. Rnd3 belongs to the family of Rho GTPases, involved in the regulation of actin cytoskeleton dynamics and important in the modulation of cellular processes such as migration and proliferation. Murine models have shown that Rnd3 is relevant for the correct development and function of the Central Nervous System and lack of its expression produces several motor alterations and neural development impairment. However, little is known about the molecular events through which Rnd3 produces these phenotypes. Interestingly we have observed that Rnd3 deficiency correlates with the appearance of protein aggregates and aberrant mitochondria in neurons. In this work, we have explored the impact of Rnd3 loss of expression in mitochondrial function and autophagy, using a Rnd3-KO CRISPR cell model. Rnd3 deficient cells show no alterations in autophagy and mitochondria turnover is not impaired. However, Rnd3 KO cells have an altered mitochondria oxidative metabolism, resembling the effect caused by oxidative stress and indicating that Rnd3-KO makes these cells strictly dependent on glycolysis to obtain energy. Altogether, our results demonstrate that Rnd3 is relevant to maintain mitochondria function, suggesting a possible role in the onset of neurodegenerative diseases.